2019
DOI: 10.1007/s11892-019-1203-9
|View full text |Cite
|
Sign up to set email alerts
|

Economics of Beta-Cell Replacement Therapy

Abstract: Purpose of Review: Type 1 diabetes impacts 1.3 million people in the United States with a total direct lifetime medical cost of $133.7 billion. Management requires a mix of daily exogenous insulin administration and frequent glucose monitoring. Decision making by the individual can be burdensome. Recent Findings: Beta-cell replacement, which involves devices protecting cells from autoimmunity and allorejection, aims at restoring physiological glucose regulation and improve clinical outcomes in patients. Given … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…While their study suggested that the most cost‐effective method to produce human PSC‐derived pancreatic progenitors could be achieved with high volume suspension cultures, 1 the recommendation/pricing will change depending on ongoing breakthroughs of scale‐up technologies available. Similar bioprocess cost analyses have been performed by others 96‐98 . Bandeiras et al reported a comprehensive bioprocessing cost model for manufacturing beta cells from PSCs taking into account numerous variables such as the number of batches produced per year, the number of patients that could be implanted from cells generated per batch, and the number of patients that could implanted with the cells per year 96 .…”
Section: Demonstration Of Scalable Production Of Human Psc‐derived Pancreatic Progenitorsmentioning
confidence: 76%
See 1 more Smart Citation
“…While their study suggested that the most cost‐effective method to produce human PSC‐derived pancreatic progenitors could be achieved with high volume suspension cultures, 1 the recommendation/pricing will change depending on ongoing breakthroughs of scale‐up technologies available. Similar bioprocess cost analyses have been performed by others 96‐98 . Bandeiras et al reported a comprehensive bioprocessing cost model for manufacturing beta cells from PSCs taking into account numerous variables such as the number of batches produced per year, the number of patients that could be implanted from cells generated per batch, and the number of patients that could implanted with the cells per year 96 .…”
Section: Demonstration Of Scalable Production Of Human Psc‐derived Pancreatic Progenitorsmentioning
confidence: 76%
“…Similar bioprocess cost analyses have been performed by others. 96 , 97 , 98 Bandeiras et al reported a comprehensive bioprocessing cost model for manufacturing beta cells from PSCs taking into account numerous variables such as the number of batches produced per year, the number of patients that could be implanted from cells generated per batch, and the number of patients that could implanted with the cells per year. 96 Based on their model, the projected cost of manufacturing beta cells for one patient could be as high as $427,231.…”
Section: Demonstration Of Scalable Production Of Human Psc ‐Derived Pancreatic Progenitorsmentioning
confidence: 99%
“…In both cases, successful long-term engraftment is essential for the therapies to become profitable (30). The cost of stem cell-derived b-cell therapy will depend on a number of variables, including the requirement of immunosuppression, the duration of graft survival, and, most importantly, the optimization of the manufacturing process (31). While avoidance of autoimmune rejection will reduce the price, higher upfront costs are needed for the development of a scalable manufacturing process and the creation of stem cell banks for clinical use.…”
Section: Why the Need For Stem-cell Based Therapy In Diabetes?mentioning
confidence: 99%
“…As time goes by, improvements in all facets of islet Tx procedure would lead to reduced costs and better outcomes meaning even more cost-effectiveness [94]. Studies such as these must be dependent on local costs and stakeholders willingness to pay the costs which explains their different findings [95]. Interesting to note, despite islet Tx not being found to be cost-effective in the Alberta study, allogeneic islet Tx is still offered to patients with the appropriate medical indication because it can provide better health outcomes to recipients regardless of cost.…”
Section: Willingness To Paymentioning
confidence: 99%